Effectiveness of the Make A Match Cooperative Learning Model in Improving Learning Outcomes in Reading Quran Surah Al-Hujurat in Elementary Schools - Achmad Suroji; Carlos Guizado (FITK UIN Walisongo Semarang, 2026)
This study aims to determine the effectiveness of the application of the Make a Match type Cooperative Learning learning model in improving student learning outcomes in QS reading materials. Al-Hujurat verse 13 in grade IV of SD Negeri Bintoro 07 Demak. This study uses the Classroom Action Research (PTK) approach which is carried out in two cycles. The research instruments used consisted of learning outcome tests, observation sheets, and documentation. Data collection techniques are carried out through learning outcome tests, observations, and documentation. The results of the study show that the application of the Make a Match type Cooperative Learning learning model is effective in improving student learning outcomes. This can be seen from the increase in student learning completeness which originally reached 70% in the first cycle to 90% in the second cycle. In addition to improving test results, student involvement in the learning process has also experienced significant development, marked by increased discussion activity, group cooperation, courage to read Qur'anic verses, and the ability to understand the meaning of verses. Improvements in learning strategies in cycle II, such as providing clearer instructions, additional discussion time, and intensive guidance for students who experience difficulties, also support learning success. Thus, the Make a Match model is proven not only to improve students' academic ability to read and understand QS. Al-Hujurat verse 13, but also increases students' motivation, confidence, and social ability to work together during the learning process. This research contributes to the development of active and cooperative learning models in Islamic Religious Education subjects in elementary schools to create more effective, interactive, and fun learning.Keywords: Cooperative Learning, Make a Match, Islamic Religious Education, learning outcomes, reading QS. Al-Hujurat.